2017
DOI: 10.1111/codi.13668
|View full text |Cite
|
Sign up to set email alerts
|

Increasing experience of ligation of the intersphincteric fistula tract for patients with Crohn's disease: what have we learned?

Abstract: The LIFT procedure offers reasonable long-term success in the treatment of perianal trans-sphincteric fistulas associated with CD. LIFT is more likely to fail in patients with concurrent colonic CD than in patients with small bowel CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 23 publications
0
31
0
2
Order By: Relevance
“…Study and patient characteristics are shown in Table S1 (supporting information) , . Five studies were RCTs, six were prospective cohort studies and 19 were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Study and patient characteristics are shown in Table S1 (supporting information) , . Five studies were RCTs, six were prospective cohort studies and 19 were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…The same group recently presented the results of a retrospective analysis of a prospective database of 23 patients with CD who underwent the LIFT procedure, over a 58-month period 95. All patients were operated on by the same surgeon.…”
Section: Modern Surgical Techniques For Perianal Fistulas In CDmentioning
confidence: 99%
“…Recently, Kamiński et al reported on 23 patients who underwent LIFT, and had a healing rate of 48%. 8 This was a small series, but the only factor predicting better outcome was the presence of associated small bowel rather than colonic disease. Figg and Church noted that colonic disease is more likely to be associated with pCD and the relatively poor results reported by Kamiński et al may be at least in part explained by the presence of perineal Crohn's.…”
Section: Literature Reviewmentioning
confidence: 83%